2011
DOI: 10.1016/j.jsps.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity of silibinin in nitrite-induced hemoglobin oxidation and membrane fragility models

Abstract: Free radical formation in heme proteins is recognized as a factor in mediating the toxicity of many drugs. Xenobiotics and drug therapy-related toxicity, due to oxidative modification of hemoglobin (Hb), has been attributed in part to the uncontrolled oxidative reactions. A variety of antioxidant strategies to ameliorate potential oxidative damage in vivo have been suggested. The present study was designed to evaluate the dose-response relationship of the free radical scavenging properties of silibinin dihemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…A number of previous studies support the view that thiamine and benfotiamine can act as antoxidative and anti-inflammatory agents. Antioxidative effects of benfotiamine were demonstrated in vivo (Schmid et al, 2008;Bozic et al, 2015b) and in vivo (Wu and Ren, 2006;Marouf et al, 2011). Here we show that benfotiamine has a protective action against the harmful effects of the prooxidant compound paraquat in neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 57%
“…A number of previous studies support the view that thiamine and benfotiamine can act as antoxidative and anti-inflammatory agents. Antioxidative effects of benfotiamine were demonstrated in vivo (Schmid et al, 2008;Bozic et al, 2015b) and in vivo (Wu and Ren, 2006;Marouf et al, 2011). Here we show that benfotiamine has a protective action against the harmful effects of the prooxidant compound paraquat in neuroblastoma cells.…”
Section: Discussionsupporting
confidence: 57%
“…The use of natural products (functional foods) has been given special attention in this regard. Recent studies have shown that various antioxidants are effective against the damaging effects of nitrite both in vivo and in vitro (Marouf et al, ). We have previously reported that NaNO 2 induces oxidative damage in human erythrocytes (Ansari et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In 1.5 ml freshly prepared hemolysate, 1.0 ml of different concentrations of MEHS (10–100 μg/ml) were added each time concomitantly with 0.1 ml sodium nitrite (6.0 mM) and the formation of methemoglobin (MetHb) was monitored spectrophotometrically (631 nm) at 10, 25 and 50 min interval. [ 17 18 ]…”
Section: Methodsmentioning
confidence: 99%